Assessment Of Mania With Self Rating Scale (Journal of Psychiatrists' Association of Nepal, 2017)
Introduction: Patients with mania are generally considered unreliable informants about their illness and most of the mania rating scales are clinician administered. There are few self-rating scales in mania and the utility of which is immense.Objective: The study was aimed to compare the co-relation between the self-rating scales and clinician rating scales in mania.Method: Forty-two patients with mania in the tertiary care center of North Indian setting were applied with Clinician Administered Rating Scale for Mania,Altman Self-Rating Mania scale, Hamilton Rating Scale for Depression and Clinical Global Impression Scale at base line and consecutive four weeks. The scores were analyzed for correlation.Result: The Pearson’s correlation coefficient rho between self rated vs. clinician in the first week scores was 0.368 with p value of